Faktor risiko osteoporosis pada wanita usia 40-80 tahun: status menopause dan obesitas - Fillah Fithra Dieny; Deny Yudi Fitranti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Osteoporosis is a disease of the musculoskeletal system which are common in women. Menopausal status which affects the production of oestrogen and obesity status that describes mass and distribution of body fat have the potential to affect bone density, which in turn may have an impact on the incidence of osteoporosis.Objective: To analyze the menopausal and obesity status as risk factors for osteoporosis in women aged 40-80 years.Method: Cross-sectional study was conducted on 224 women aged 40-80 years in Ngemplak Simongan, Semarang. Status of obesity was determined by percent of body fat, body mass index (BMI), waist circumference, and waist-hip ratio (WHR). Menopausal status was determined based on the occurrence of menstruation in the past one year, and the age was calculated from the difference between date of birth and date of measurement. Bone density was assessed frombone mineral density measurement. Chi-square test and logistic regression were used to determine the relationship and the most influential factors. The risk was expressed in ratio prevalence (RP).Results: The prevalence of low bone density and obesity in each age range, were 43.8% and 57.9% for ages 40-50 years, 67.7% and 58.6% for ages 51-60 years, 84.9% and 49.1% for ages 61-70 year, 86.7% and 66.7% for ages 71-80 years. There were significant relationships between age, menopausal status, BMI, WHR and bone density (p=0.000, p=0.032, p=0.043, p=0.017, respectively). Osteoporosis (13.3%) and osteopenia (58.7%) were most widely experienced by subjects with high WHR and menopause. Percentage of osteopenia in high WHR and non-menopause subjects (60%) was higher than normal WHR and menopause subjects (52.9%). Age 61-80 years, high WHR, and non-obese BMI were the most influenced risk factorsfor the incidence of low bone density (p=0.001, p=0.038, p=0.043). Ratio prevalence of elderly, high WHR and non-obese BMI were 1.448, 1.326, 1.208.Conclusion: High WHR explains the role of android obesity and visceral fat as risk factors for low bone density. Premenopausal women will be more at risk of having low bone density if they have high WHR.